Influence of cataract surgery on retinal thickness: Vpliv operacije katarakte na debelino mrežnice - Šiško, Katarina; Knez, Nina; Pahor, Dušica (Acta Medico-Biotechnica, 2021)
Purpose: We evaluated the potential influence of cataract surgery on macular thickness and on the thickness of the retinal nerve fibre layer (RNFL) at different time intervals within 1 month after surgery.Methods: This prospective study involved 27 patients (27 eyes) scheduled for ambulatory cataract surgery with phacoemulsification and intraocular lens implantation. Optical coherence tomography was used to measure macular thickness, macular volume and RNFL thickness on operated eyes on the day before surgery and 1, 14 and 30 days after surgery. Contralateral non-operated eyes served as a control group (19 patients, 19 eyes).Results: One month after surgery, 75% of the macula showed a significant increase in thickness (p0.05).Conclusion: These results confirmed the influence of uncomplicated cataract surgery on macular thickening 1 month after surgery.
Keywords: cataract surgery; optical coherence tomography (OCT); retinal thickness; retinal volume; RNFL